Principles and practices of the photo-thermal adaptability improvement in soybean - Li-xin ZHANG; Wei LIU; Mesfin Tsegaw; Xin XU; Yan-ping QI; Enoch Sapey; Lu-ping LIU; Ting-ting WU; Shi SUN; Tian-fu HAN (Journal of Integrative Agriculture, 2020)
As a short-day (SD) and thermophilic plant, soybean (Glycine max (L.) Merr.) is sensitive to photo-thermal conditions. This characteristic severely limits the cultivation range of a given soybean cultivar and affects the performances of agronomic traits such as yield, plant architectures, and seed quality. Therefore, understanding the mechanism of photo-thermal sensitivity will provide a theoretical basis for soybean improvement. In this review, we introduce the advances in physiological, genetic, and molecular researches in photoperiodism of soybean, and progress in the improvement of the photo-thermal adaptability. We also summarize the photo-thermal conditions and characteristics of widely-planted soybean cultivars of major production regions in China. Furthermore, we proposed a novel concept of ‘ecotyping’ and the strategies for widely-adapted soybean cultivar breeding. This review provides an important guide for improving the adaptability of soybean.